Chronic Migraine Preventive Treatment by Prefrontal–Occipital Transcranial Direct Current Stimulation (tDCS): A Proof-of-Concept Study on the Effect of Psychiatric Comorbidities - Mastria, Giulio; Viganò, Alessandro; Corrado, Alessandra; Mancini, Valentina; Pirillo, Cristina; Badini, Simone; Petolicchio, Barbara; Toscano, Massimiliano; Altieri, Marta; Delle Chiaie, Roberto; Di Piero, Vittorio (Frontiers in Neurology, 2021)
Chronic Migraine (CM) is often complicated by medication overuse headache (MOH) and psychiatric comorbidities that may influence the clinical outcome. This study aimed to investigate the relationship between psychiatric comorbidities and the effect of transcranial direct current stimulation (tDCS) in patients with CM with or without MOH. We recruited 16 consecutive CM patients who had an unsatisfactory response to at least 3 pharmacological preventive therapies. They were treated with anodal right-prefrontal and cathodal occipital tDCS (intensity: 2mA, time: 20 min) 3 times per week for 4 weeks. All patients underwent a psychopathological assessment before and after treatment and 5 of them were diagnosed with bipolar disorder (BD). After treatment, all the patients showed a significant decrease of severe and overall headache days per month. Despite having a higher migraine burden at baseline, patients with CM and BD showed a significantly greater reduction of severe headaches and psychiatric symptoms. Overall, tDCS seems to be effective in the treatment of CM patients with a poor response to different classes of pharmacological therapies, while BD status positively influences the response of migraineurs to tDCS.